The Self-sustained High temperature Synthesis (SHS) technology as novel approach in the management of asbestos waste. (15th June 2018) - Gaggero, Laura; Ferretti, Maurizio
Abstract: The SHS technique was experimented in chrysotile breakdown. By means of two reactions such as Mg3 Si2 O5 (OH)4 + Fe2 O3 + 3 Mg and 2Mg3 Si2 O5 (OH)4 + Fe3 O4 + 4 Mg the chrysotile was completely converted into forsterite-rich olivine. Different mixtures of hematite + Mg and magnetite + Mg were tested with chrysotile to establish the maximum chrysotile amount in order to allow the reaction. In comparison with conventional thermal treatments, the SHS process is characterized by a fast reaction, needs low activation energy and the apparatus is simple. For these reasons, the asbestos neutralisation is carried out with positive balance of time and costs of the process. Furthermore, the combustion product can be re-used as secondary material. Graphical abstract: Highlights: The chemical-physical breakdown of asbestos was obtained by a Self-sustained combustion synthesis SHS reaction. The reaction starts by a trigger then proceeds as a wave through the reactant volume without any additional energy. Secondary (industrial) minerals derive from the chrysotile breakdown. SHS is a cost effective technique in management of hazardous waste, with environmental benefits, as less CO2 production. Globally, the ACW treatment has a potential market, with environmental and social benefits compared with land filling.